Audit trails - Espinoza-Guido, Sergio (2012)
To carry out an examination, audit or review, it becomes necessary, in order to give an opinion on the work done, to compile appropriate evidence as a basis to support the conclusions, opinions and recommendations. Due to the fact that many times it becomes difficult to make this compilation, it is necessary to use a very valuable and supportive element, called audit trail, which is one of the test procedures that apply in this type of tests. The intention with the application is to guide toward the correct direction to find evidence that is useful in the work to be done. This type of test procedure has an important and helpful role in the process of collecting evidence in order to have a better judgment when identifying and clarifying certain findings. This article is intended to provide a new approach to the use and application of this type of instrument.